PENGARUH INFLASI, TINGKAT SUKU BUNGA, NILAI TUKAR RUPIAH TERHADAP DOLAR AMERIKA TERHADAP HARGA SAHAM (Perusahaan Industri Tekstil Dan Garmen Yang Tercatat Di Bursa Efek Indonesia Periode Tahun 2013-2015) - Hamdan Prabowo; Budi Wahono; Muhammad Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACT This research aim to to: a) to know by parsial influence of Inflation ( X1) Mount Rate Of Interest ( X2) and Exchange Rate Rupiah To American Dollar ( X3) to Price Share ( Y). b) to know and analyse by simultan Inflation, Storey;Level Rate Of Interest and Exchange Rate Rupiah to American Dollar to Price Share [in] Effect Exchange Indonesia. This Research represent type of explanatory research with quantitative approach.Source of this research data [is] obtained from financial statement industrial company of Textile and of Garmen which [is] listing [in] Effect Exchange Indonesia during period 2013-2015. Data the used [is] data of sekunder. This analysis [is] [done/conducted] by using program of SPSS. Result of this research [of] menunjukan that inflation variable, [do] not have an effect on share price terhdap signifikan, while rate of interest storey;level, rupiah exchange rate have influence of signifikan to share price.Keyword : Inflation, Exchange Rate Rupiah, Exchange Rate Rupiah and Price Share